Green Lantern, war journal. Vol. 1, Contagion - Johnson, Phillip Kennedy, 1970- (Dawn of DC., 2024)
"John Stewart returns as Green Lantern for a story about rediscovering your past and forging your future as a Guardian! Just when John Stewart thought he was out as a Green Lantern...he's pulled back in! Hanging up the emerald power ring, the once great Green Lantern is giving the post-superhero life a try. This all comes to a screeching halt when a mysterious Guardian from another universe lands on Earth, seeking John's help. With new threats emerging from the shadows, this new lantern will help John Stewart rediscover what once fueled the fire to make him the greatest Green Lantern in the Multiverse!"--